Quadratic stability and stabilization of bimodal piecewise linear systems - Eren, Yavuz; Shen, Jinglai; Camlibel, Kanat (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
This paper deals with quadratic stability and feedback stabilization problems for continuous bimodal piecewise linear systems. First, we provide necessary and sufficient conditions in terms of linear matrix inequalities for quadratic stability and stabilization of this class of systems. Later, these conditions are investigated from a geometric control point of view and a set of sufficient conditions (in terms of the zero dynamics of one of the two linear subsystems) for feedback stabilization are obtained. (c) 2014 Elsevier Ltd. All rights reserved.
Keywords: Piecewise linear systems; Bimodal systems; Common quadratic Lyapunov function; Quadratic stability; Feedback stabilization; LYAPUNOV FUNCTIONS; Automation & Control Systems; Engineering